answersLogoWhite

0


Best Answer

if:

y = x2

y = x + 6

then

x2 = x + 6

=> x2 - x - 6 =0

=> (x - 3)(x + 2) = 0

=> x = 3 or -2

=> y = 9 or 4 respectively, ie the points (3, 9) and (-2, 4).

User Avatar

Wiki User

14y ago
This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: What are the solutions for y equals x squared and y equals x plus 6?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

What is 6 squared plus 8 squared?

To calculate 6 squared plus 8 squared, you first need to square each number individually. 6 squared is 6 x 6, which equals 36. 8 squared is 8 x 8, which equals 64. Adding these two results together, you get 36 + 64, which equals 100. So, 6 squared plus 8 squared is 100.


X squared plus y squared plus z if x equals 7 y equals 6 and z equals 4?

89


What are the solutions for X squared minus 5x equals 6?

The solutions to the quadratic equation are: x = -1 and x = 6


IF 2 plus 3 equals 10. 7 plus 2 equals 63. 6 plus 5 equals 66. 8 plus 4 equals 96 therefore 9 plus 7 equals?

2 squared plus 2 x 3 = 10, 7 squared plus 7 x 2 = 63, 6 squared plus 6 x 5 = 66,8 squared plus 8 x 4 = 96 so 9 squared plus 9 x 7 = 81 + 63 = 144.


Where is the center of the circle given by the equation x plus 4 squared plus y plus 6 squared equals 49?

(-4,-6)


What is a squared plus b squared equals c squared when a equals 2 and c equals 6?

b = sqrt32 or 4 root 2


What is the solution to x squared equals x plus 6?

X squared = x+6 6+x=x squared X=6


A squared plus b squared equals c squared?

This is the common form of the Pythagorean Theorem. It describes the relationship between the two legs of a right triangle and the hypotenuse.


What is the discriminant of x squared plus 6 x plus 5 equals 0?

4


What is the discriminant of 4x squared plus 5x equals 6?

The discriminant is 121.


What is x squared equals 36?

x = plus or minus 6.


How many solutions does the linear system -8x plus 2y equals 6 and -4x plus y equals 3 have?

Two solutions and they are:- x = 0 and y = 3